Evaluation of the mental health status of intensive care unit healthcare workers at the beginning of COVID-19 pandemic - Meriç Özgündüz, Ceren; Bıçakçıoğlu, Murat; Sahin Tutak, Ayse; Özgündüz, Arman (Frontiers in Public Health, 2024)
Objective: During pandemic periods, mental health issues are highly prevalent, particularly among healthcare workers who are at a higher risk of developing psychiatric disorders. The aim of this study is to to evaluate the mental health status of the intensive care unit (ICU) healthcare workers, who play a vital role in managing the COVID-19 pandemic, in terms of the quality of sleep, levels of depressive and anxiety symptoms, stress and to determine the factors that affect their mental health. Method: The research was conducted in April 2020 and incorporated a total of 79 participants working in an university hospital ICUs in Turkey. Pittsburgh Sleep Quality Index (PSQI), Depression Anxiety Stress Scale 42 (DASS-42), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were applied. Results: Among the participants, 58 individuals comprising 73.4% of the cohort were working in the ICUs, managing patients infected with COVID-19. Those working in ICUs with COVID-19 (+) patients had significantly higher DASS-S, BAI, and BDI scores. Doctors' BDI scores were significantly lower compared to both nurses and other healthcare workers. Participants exhibiting COVID-19 symptoms manifested significantly higher BAI scores in compared to those without such symptoms. Conclusion: Healthcare workers involved in ICUs with COVID-19 (+) patients were more significantly affected psychologically, doctors had lower depressive symptoms as compared to other healthcare workers. In addition, individuals with COVID-19 symptoms demonstrated significantly higher levels of anxiety. The findings of our study emphasize the significance of providing psychological support to healthcare workers throughout pandemics.